Quasi-Newton power flow using partial Jacobian updates. - Semlyen, A.
We present a quasi-Newton power flow methodology that incorporates several strategies to obtain substantial computing savings. Newton steps are combined with constant Jacobian (or ?simple?) steps and partial Jacobian updates to get an efficient quasi-Newton method. The methodology proposed includes the possibility of selecting the next best step by measuring the residuals. Partial Jacobian updates (PJU) are included in the quasi-Newton power now using LU factorization updates and/or the matrix modification lemma. The method has been tested with systems ranging in size from 14 to 6372 buses. For large power systems we have obtained savings (in flops) in the order of 50% compared to Newton's method
Keywords: 14 bus power system; 6372 bus power system; LU factorization updates; Computing savings; Matrix modification lemma; Next best step selection; Partial Jacobian updates; Quasi-Newton power flow; Residuals measurement